Fat Compartment Gliding Theory – A Novel Technique for the Repositioning of Superficial Fat Compartments for Facial Rejuvenation - Eid L; Mao X; Zhao B; Mao J; Qian S; Zhang Y; Zhang Y; Zhang L; Cheng L; Zhang Y; Sun X (Dove Medical Press, 2023)
Loy Eid,* Xiyuan Mao,* Binfan Zhao, Jiayi Mao, Shutong Qian, Yuyu Zhang, Ying Zhang, Lu Zhang, Liying Cheng, Yuguang Zhang, Xiaoming Sun Department of Plastic and Reconstructive Surgery, Shanghai Ninth People's Hospital, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuguang Zhang; Xiaoming Sun, Department of Plastic and Reconstructive Surgery, Shanghai Ninth People's Hospital, Shanghai, People's Republic of China, Email zhangyg18@126.com; drsunxm@126.comBackground: Facial fat compartments and their role in facial aging have gained increased recognition and are playing a significant role in facial rejuvenation. The superficial fat compartments glide inferiorly during the aging process, leading to the flattening and elongation of the face and the appearance of facial bulges, folds, and grooves.Patients and Methods: Ultrasound imaging of the facial soft tissues was performed on nine female volunteers to demonstrate the change in superficial facial fat compartments from an upright to supine position. The net suture jowl and medial cheek fat compartment repositioning technique was operated on 165 Asian patients between September 2020 and July 2021. Volume and projection change of malar and jowl regions, as well as change in elevation of malar protrusion were measured 1, 3, and 6 months postoperatively using a three-dimensional imaging system.Results: Ultrasound measurements confirmed the medial and middle cheek, nasolabial, and jowl fat compartments changed in thickness during positional changes with age-related differences. Postoperative three-dimensional imaging showed volume and projection increase in the malar region (2.23mL and 1.11mm) and decrease in the jowl region (− 0.18mL and − 0.52mm) by the 6-month follow-up date, and malar projection saw a superior displacement of 3.08mm.Conclusion: The superficial fat glide inferiorly within their compartments under the force of gravity and naturally reposition themselves when the effect of gravity is reversed. The net suture technique offers a minimally invasive method for lifting the jowl fat, volumizing the mid-cheek and achieving facial rejuvenation by repositioning the superficial fat compartments.Keywords: fat compartments, facial rejuvenation, face lift, facial aging